Pathways of influences leading to adoption of the Faith, Activity and Nutrition (FAN) program in a statewide initiative. (August 2021) - Hutto, Brent; Saunders, Ruth P.; Wilcox, Sara; Jake-Schoffman, Danielle E.; Bernhart, John A.; Dunn, Caroline G.; Kaczynski, Andrew T.; James, Katherine L.
Highlights: FAN statewide church adoption was 11.7 % and congregant reach was 20.0 %. A culture of concern for congregant health and openness to new ideas favored adoption. Qualitative Comparative Analysis consistency (97 %) for adoption was adequate. Qualitative Comparative Analysis and coverage 71 % adoption was adequate. Abstract: RE-AIM (Reach, effectiveness, Adoption, Implementation, Maintenance) and CFIR (Consolidated Framework for Implementation Research) are complementary frameworks guiding research on dissemination and implementation of evidence-based interventions and factors influencing this process. Faith, Activity, and Nutrition (FAN) is an evidence-based program that increased physical activity and fruit and vegetable intake in faith-based settings. The aims of this adoption study were to quantify state-wide church level adoption rates and congregant reach of FAN in accordance with RE-AIM guidelines, and to explore the association of CFIR-derived constructs of the church inner setting and pastor characteristics with FAN adoption. Church recruitment was documented, and data were collected via telephone-administered surveys from 93 pastors in adopting churches and 60 pastors in non-adopting churches. Qualitative Comparative Analysis (QCA) identified combinations of CFIR-derived church and pastor characteristics sufficient for FAN adoption. As defined by RE-AIM, church-level FAN adoption was 11.7 % and congregant-level reach was 20.0 %. Fourteen pathways to adoption were identified; seven of these featured the presence of a culture of concern for congregant health along with openness to new ideas. Results suggest early assessment of these two CFIR-derived inner setting constructs may help identify faith-based organizations predisposed to undertake a comprehensive, environmental intervention to promote congregant health.